Diagnostic application of transabdominal ultrasound in pediatric patients with hematochezia. / Aplicación diagnóstica del ultrasonido transabdominal en pacientes pediátricos con hematoquecia. - Zhang, Chunlin; Zhang, Chaoxue (Investigación Clínica, 2020)
Abstract. The objective of the work was to analyze the diagnostic accuracy of transabdominal ultrasound in diseases causing hematochezia. The present retrospective study included 427 pediatric patients with hematochezia or hematochezia accompanied by abdominal pain, who came to our hospital from October 2014 to September 2018. Transabdominal ultrasound was performed in all patients. Demographic data such as age, gender and clinical variables including symptoms and the hematochezia aspect were recorded. The diagnostic accuracy was analyzed. Among all patients, the hematochezia types were dark red bloody stools 163 (38.2%), black stools 102 (23.9%), jam-like bloody stools74 (17.3%), scarlet blood 55 (12.9%) and fecal occult blood 33 (7.7%). There were 153 (35.8%) patients with intussusception, 116 (27.2%) patients with Meckel’s diverticulum, 95 (22.2%) patients with intestinal duplication, and 63 (14.8%) patients with intestinal polyps. Transabdominal ultrasound showed there were 150 patients with intussusception, with an accuracy of 98.0%; 103 patients with Meckel’s diverticulum, with an accuracy of 88.8%; 84 patients with intestinal duplication, with an accuracy of 88.4%; and 54 patients with intestinal polyps, with an accuracy of 85.7%. The diagnostic sensitivity was significantly higher for intussusception than for other diseases. It is concluded that transabdominal ultrasound had a high accuracy in the diagnosis of hematochezia-related diseases, including intussusception, Meckel’s diverticulum, intestinal polyps and intestinal duplication. Resumen. El objetivo del presente trabajo fue analizar la precisión diagnóstica de la ecografía transabdominal en enfermedades relacionadas con hematoquecia. El presente estudio retrospectivo incluyó un total de 427 pacientes pediátricos con hematoquecia o hematoquecia acompañada de dolor abdominal, que acudieron a nuestro hospital entre octubre de 2014 y septiembre de 2018. Se realizó una ecografía transabdominal en todos los pacientes. Se registraron datos demográficos como la edad, el sexo y las variables clínicas, incluidos los síntomas y el aspecto de la hematoquecia. Se analizó la precisión diagnóstica. Entre todos los pacientes, los tipos de hematoquecia presentes fueron: heces con sangre de color rojo oscuro 163 (38.2%), heces negras 102 (23.9%), heces con sangre como mermelada 74 (17.3%), sangre escarlata 55 (12.9%) y sangre oculta en heces 33 (7,7%). Hubo 153 (35,8%) pacientes con invaginación intestinal, 116 (27,2%) pacientes con divertículo de Meckel, 95 (22,2%) pacientes con duplicación intestinal y 63 (14,8%) pacientes con pólipos intestinales. La ecografía transabdominal mostró que había 150 pacientes con invaginación intestinal, con una precisión del 98,0%; 103 pacientes con divertículo de Meckel, con una precisión del 88,8%; 84 pacientes con duplicación intestinal, con una precisión del 88,4%; y 54 pacientes con pólipos intestinales, con una precisión del 85,7%. La sensibilidad diagnóstica fue significativamente mayor para la invaginación intestinal que para otras enfermedades. Se concluye que la ecografía transabdominal tuvo una alta precisión en el diagnóstico de enfermedades relacionadas con la hematoquecia, incluidos la invaginación intestinal, el divertículo de Meckel, los pólipos intestinales y la duplicación intestinal.